The AKTUALISASI AMANAT AGUNG (MATIUS 28:19-20) DALAM GERAKAN KARISMATIK - Samuel Tampubolon (Jurnal Teologi Amreta (ISSN: 2599-3100), 2025)
The Great Commission is a noble commandment and mandate from the Lord Jesus that must be carried out by the church and believers. The Great Commission is not just a slogan but a task that is urgent and cannot be postponed ahead of His nearer coming. In its long history the church has and will continue to strive to carry out this mandate. A church that truly carries out the Great Commission will be seen from its growth both in quality and quantity. It is necessary to underline that church growth is God’s will for His church. Today the charismatic movement church is experiencing very rapid growth in terms of quantity both in local church planting and growth in the number of congregations. Trough this paper the author wishes to reveal that in the growth of the church this charismatic movement is part of the actualization of the Great Commission. This research also seeks to provide theological arguments against sharp criticism that corner the charismatic movement excessily.